AB0220 The promise of ultrasound guided minimally invasive synovial biopsies in the united states. (15th June 2017) - Mandelin, AM; Homan, P; Cuda, CM; Dominguez, ST; Bridges, SL; Bathon, JM; Atkinson, J; Fox, D; Matteson, EL; Buckley, CD; Pitzalis, C; Parks, D; et al.
Abstract : Background: Currently we are in the golden age of therapy for patients with rheumatoid arthritis (RA). However, currently there exists no available assay to predict the response to a particular therapy for an individual patient. Today, rheumatologists do not have information at han for therapeutic decisions. It is clear that the target organ in RA patients, i.e. the synovium, has the potential to unlock the secret for determining therapeutic response. Ideally, a sufficient synovial sample would be obtained from each patient to perform histology, sorting of individual cell populations and transcriptional analyses. Objectives: Our goal is to establish a minimally invasive ultrasound guided synovial biopsy program in the United States to obtain synovial tissue for determining therapeutic response. Methods: Rheumatologists from six Universities in the United States were trained in ultrasound guided minimally invasive synovial tissue biopsy procedures. Only patients with a grey scale synovitis score of 2 or greater were selected. A disposable semi-automatic-guillotine type biopsy needle (Quick-Core) was utilized for all patients and 25/26 patients had the biopsy performed on the wrist. Histology was performed on whole tissue. RNA was extracted from whole tissue and from FACS sorted macrophages in order for RNA sequencing (RNA-seq) analysis to be performed. Results: Our group has already performed over 26 minimally invasive ultrasound guided synovial tissue biopsies on RA patients with active disease. We had minimal adverse effects and patients tolerated the procedure very well. At least 6–12 needle biopsies of synovial tissue were obtained via biopsy per patient. A minimum of 4 needle biopsies were placed in formalin and synovial lining was confirmed via histologic analyses. The remaining pieces were used to prepare libraries for RNA-seq. We observed comparable RNA integrity numbers, a measure of RNA quality, between the whole synovial tissue from RA (biopsy obtained) and OA (surgically-obtained) patients. OA patients segregated together transcriptionally, while RA patients are more heterogeneous as demonstrated via RNAseq analysis. We also optimized a protocol for digestion of synovial tissue biopsies for isolation of macrophages. We identified genes differentially associated with macrophage activity in RA versus OA synovial macrophages that were not evident in the whole tissue transcriptional profile. Conclusions: Ultrasound guided synovial tissue biopsies are feasible in the United States. Based on our recent success using minimally invasive ultrasound guided synovial biopsies, we believe that this procedure coupled with cutting-edge technologies will provide the critical information to rheumatologists to establish precision based medicine as a reality for RA patients. Disclosure of Interest: None declared